2011
DOI: 10.1016/j.procs.2011.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Estimating customer future value of different customer segments based on adapted RFM model in retail banking context

Abstract: One of the important challenges in customer-based organizations is customer cognition, understanding difference between them, and ranking them. Customer need-based segmentation was common in past years, but recently customer value as a quantifiable parameter could be used for customer segmentation. In this regard, customer segmentation based on customer lifetime value (CLV) and estimating the value of each segment would be useful for making decision in marketing and customer relationship management (CRM) progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 9 publications
0
51
0
1
Order By: Relevance
“…Huang & Gartner (2012) regarded Sales Promotion as a direct stimulus to extra value of a product or an incentive to final consumers, salespeople, or distributors. Khajvand & Tarokh (2011) mentioned that Sales Promotion was composed of various temporary incentives, mainly to induce consumers or dealers purchasing certain products in advance or purchasing more quantity. indicated that Sales Promotion was essentially a complimentary marketing effort, being practiced in limited time and tending to stimulate consumer purchase.…”
Section: Sales Promotionmentioning
confidence: 99%
“…Huang & Gartner (2012) regarded Sales Promotion as a direct stimulus to extra value of a product or an incentive to final consumers, salespeople, or distributors. Khajvand & Tarokh (2011) mentioned that Sales Promotion was composed of various temporary incentives, mainly to induce consumers or dealers purchasing certain products in advance or purchasing more quantity. indicated that Sales Promotion was essentially a complimentary marketing effort, being practiced in limited time and tending to stimulate consumer purchase.…”
Section: Sales Promotionmentioning
confidence: 99%
“…Customer segmentation and clustering can be performed according to disparate criteria, including but not limited to profitability (Zeithaml et al, 2001), customer behavior (Ghazanfari et al, 2010;Gough & Sozou, 2005;Neal, 1998), degree of customer loyalty (Ansari & Riasi, 2016a;Cheng & Chen, 2009;Khajvand & Tarokh, 2011;McCarty & Hastak, 2007;Wei et al, 2012), purchase frequency (Ansari & Riasi, 2016a;Khajvand & Tarokh, 2011;McCarty & Hastak, 2007), purchase volume (Ghazanfari et al, 2010;Zeithaml et al, 2001), demographics (Dehghanpour & Rezvani, 2015;Gough & Sozou, 2005) and etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To analyze the clusters and to measure the value of the customers in each cluster, they used RFM (recency, frequency, and monetary value) model. The RFM is a very popular model for customer value analysis and it has been used by many scholars in order to perform market segmentation (Cheng & Chen, 2009;Khajvand & Tarokh, 2011;McCarty & Hastak, 2007). Since RFM analyzes the behavior of the consumers, it can be considered as a behavior-based model (Wei et al, 2012;Yeh et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, the obtained results along with the strategies that are to be applied by the company in various clusters are studied. Khajvand and Tarokh (2011) presented a model where the customers' loyalty rate is calculated after studying their history in different periods and their behaviors in the future is estimated. This framework consists of 7 phases.…”
Section: The Extended Rfm Modelmentioning
confidence: 99%